The 1950s in the Zábrana Family: The Diary as a Space of Reflexivity - Spěváček, Jan (Bohemica Olomucensia, 2025)
This study examines literary and personal reflections on the period of the 1950s in the Zábrana family, focusing on three key texts: Ohlédnutí (1994) by Jiřina Zábranová, Celý život (1992) by Jan Zábrana, and Flashky (2014) by Eva Zábranová. These works offer a unique opportunity to look at the same decade through the eyes of three generations. Based on Philippe Lejeune's concept of the diary as "anti-fiction", Jan Patočka's concept of reflexivity, and Paul Ricœur's triple mimesis, this study outlines how each of the texts mentioned transforms personal experience into a testimony of time. Jiřina Zábranová's memoir documents the brutal realities of a political prisoner, Jan Zábrana's diary captures existential disillusionment and historical despair of Czech poet and translator, while Eva Zábranová's Flashky reflect the lingering effects of the past on family relationships. The study contributes to broader discussions on autobiographical writing, memory studies, and the role of literature in preserving historical experience.
Keywords: Jan Zábrana; diary; family memory; reflexivity; life writing; 1950s in Czechoslovakia